Mentality and ethnic memory in a methodological context (Journal of Philosophy Culture and Political Science, 2018)
The article discusses the theory of mental memory ethnos, its socio-psychological development, reflected in the ways of thinking , and cultural values in the temporal, spatial and social levels. The characteristic of the concept of «mentality» as a socio- psychological phenomenon that displays spiritual world or social community , age or ethnic culture, which is an integral feature of ethnopsycological individual, nation and nation. Ethnomentality memory considered in the psychosocial and philosophical -cultural aspects. Shows the important components of ethnic mentality, mental specificity of values manifested in ethnic style, culture and lifestyle, and is a criterion for ethnic identity. Conducted theoretical and methodological analysis of scientific works of Kazakh, Russian and foreign researchers studying theory mentality , mental processes and their relationships. Key words: mentality, ethnomentality memory, ethnophors, ethnic culture